2021
DOI: 10.1111/phpp.12756
|View full text |Cite
|
Sign up to set email alerts
|

Light‐ and laser‐based treatments for granuloma annulare: A systematic review

Abstract: Background: Granuloma annulare (GA) is challenging to treat, especially when generalized. A systematic review to support the use of light-and laser-based treatments for GA is lacking. Methods:We performed a systematic review by searching Cochrane, MEDLINE, and Embase. Title, abstract, full-text screening, and data extraction were done in duplicate. Quality appraisal was performed using the Joanna Briggs Institute critical appraisal tool for case series.Results: Thirty-one case series met the inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…With respect to granuloma annulare, although UVA1 appears to have some efficacy for generalized granuloma annulare, further studies are necessary to identify the optimal treatment regimen [ 35 , 36 , 37 ]. In fact, the latest review on this subject by Mukovozov et al [ 38 ] positions it as an alternative to treatment with narrowband UVB phototherapy, which is considered as the first-line phototherapy for this entity. Our results support the hypothesis already put forward by other published studies that UVA1 is possibly effective for generalized granuloma annulare.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to granuloma annulare, although UVA1 appears to have some efficacy for generalized granuloma annulare, further studies are necessary to identify the optimal treatment regimen [ 35 , 36 , 37 ]. In fact, the latest review on this subject by Mukovozov et al [ 38 ] positions it as an alternative to treatment with narrowband UVB phototherapy, which is considered as the first-line phototherapy for this entity. Our results support the hypothesis already put forward by other published studies that UVA1 is possibly effective for generalized granuloma annulare.…”
Section: Discussionmentioning
confidence: 99%
“…Some good options for this are oral treatments with dapsone, hydroxychloroquine, or isotretinoin, though still, none assures consistent nor durable effects [ 2 , 8 , 9 ]. Phototherapy (specifically PUVA (psoralen and UVA) and PDT (photodynamic therapy)), on the other hand, has also been considered an optimal alternative with good results, but due to their monetary costs and higher risk of squamous cell carcinoma in long treatments, it is left as a second-line treatment, as well as UVB/nbUVB/excimer laser [ 2 , 8 , 10 ]. The new treatment option studies have been inclined in biologic therapies using adalimumab, etanercept, infliximab, and dupilumab with interesting and promising results, though further research is needed, especially when cases of GA caused by some of these molecules have been reported [ 2 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism by which the excimer laser ameliorates GA is unclear at present. It has been suggested that cooperation between histiocytes and T-helper cells may be blunted by the delivery of UVB spectrum light, including 308-nm wavelengths, resulting in decreased immunoreactivity to the unknown antigen implicated in granuloma formation in GA. 4 GA occasionally resolves within a few years after onset, making it difficult to exclude the possibility of spontaneous resolution in these cases. To clarify the efficacy and working mechanism of excimer laser therapy for GA, further research will be required, but excimer laser therapy may be a useful therapeutic option for GA.…”
Section: E156 |mentioning
confidence: 99%